METHODOLOGY OF TEACHING BIOPHYSICS BASED ON AN INNOVATIVE APPROACH - Z.M.Narzullayeva, (TADQIQOTLAR, 2025)
Abstract.  This  in  the  article  biophysics  science  innovative  pedagogical technologies based on of teaching theoretical-methodical basics , interactive methods , digital  education  from  the  means  use  ,  in  students  research  skills  formation  and interdisciplinary  integration  importance  analysis  Innovative  approaches  efficiency practical examples with based on is given .